The use of percutaneous-endoscopic rendezvous stenting in a patient with bile duct injury after cholecystectomy—and a unique complication requiring secondary endoscopic intervention. Issue 4 (20th April 2021) - Vidovszky, Anna A; Qafiti, Fred; El Haddi, S James; Doukides, Theodore; Hus, Nir; Genuit, Thomas
Abstract: Bile duct injury (BDI) is a potentially devastating complication after cholecystectomy. Familiarity with the diagnosis and multidisciplinary treatment options is imperative. This report highlights the utility of the rendezvous stenting procedure in a high-risk patient and describes a rare complication involving stent misplacement through the surgical drain. This is a 96-year-old female patient who suffered a Strasburg Class D injury during cholecystectomy, repaired over a T-tube. The T-tube dislodged postoperatively. Endoscopic and transhepatic stenting attempts were unsuccessful. Ultimately, a rendezvous approach allowed successful deployment of a covered metal stent. The stent was inadvertently deployed through a side fenestration of a surgical drain and was explanted upon drain removal. Repeat endoscopic stent placement was successful. The patient recovered without further complication. Surgical drains near the BDI can become sources of unexpected complications. A higher index of suspicion and careful interpretation of procedural imaging studies may prevent this complication.